THE EFFECT OF AUTHORITARIAN PARENTING ON THE EMOTIONAL INTELLEGENCE OF CHILDREN AT ELEMENTARY SCHOOL TIRON 4 KEDIRI REGENCY - Septania Navy Damayanti (Sean Institute, 2022)
This research is based on the observations of researchers and interviewees, that the parenting applied by parents of elementary school age students is still a lot of mistakes. Authoritarian parenting is the most widely applied by parents, even though there are many negative impacts from the application of this parenting pattern, such as a decrease in emotional intelligence including recognizing self-emotions, managing emotions, and building relationships. The problems of this research are (1) Does authoritarian parenting affect emotional intelligence in recognizing emotions in children at SDN Tiron 4 Kediri Regency? (2) Does authoritarian parenting affect emotional intelligence in managing emotions in children at SDN Tiron 4, Kediri Regency? (3) Does authoritarian parenting affect emotional intelligence in fostering relationships with children at SDN Tiron 4, Kediri Regency? The purpose of this study was to (1) prove the effect of authoritarian parenting on emotional intelligence in recognizing emotions in children at SDN Tiron 4 Kediri City. (2) Proving the effect of authoritarian parenting on emotional intelligence in managing the emotions of children at SDN Tiron 4 Kediri City. (3) Proving the effect of authoritarian parenting on emotional intelligence in fostering relationships with children at SDN Tiron 4 Kediri City. This study uses a quantitative research approach with survey methods. The subjects of this study were fifth grade students at SDN Tiron 4, Kediri Regency. In this study, the presentation of data in the form of statistical figures related to authoritarian parenting on children's emotional intelligence. Based on the hypothesis test, the results of statistical calculations show a correlation value of -0.565 with a significance value of 0.018. Because the correlation is negative and the significance value is <0.05. Where it can be concluded that H0 is rejected and Ha is accepted, which means that there is a significant influence between authoritarian parenting on the emotional intelligence of grade 5 students at SDN Tiron 4, Kediri Regency.